Low-Reflectivity Drusen With Overlying RPE Damage Revealed by Spectral-Domain OCT: Hint for the Development of Age-Related Macular Degeneration - Yang, Shasha; Gao, Zongyin; Qiu, Haijiang; Zuo, Chengguo; Mi, Lan; Xiao, Hui; Liu, Xing (Frontiers in Medicine, 2021)
Purpose To observe the relationship between characteristic changes in druse morphology revealed by spectral-domain optical coherence tomography (SD-OCT) and the progression of age-related macular degeneration (AMD). Methods A total of 380 drusen in 45 eyes in thirty-five patients with intermediate drusen were longitudinally followed up every 6 months by SD-OCT for a period of 24 months. Drusen were divided into the dynamic group and stable group according to the following parameters: number, volume, concurrent retinal pigment epithelium (RPE)/ellipsoid zone (EZ) damage and the development of advanced AMD. The morphological characteristics of progressive or stable drusen were further analyzed. Odds ratios (ORs) and the risk for druse progression were calculated. Results The level of interobserver and intraobserver agreement for each druse tomographic morphological parameter ranged from 82.7% to 90%. At the end of an average follow-up of 15.92±6.99 months, 6 patients developed choroidal neovascularization, and no patients developed geographic atrophy. Finally, 139 drusen changed, and 241 drusen remained stable. Drusen with low reflectivity (P<0.001; OR: 5.26; 95% CI: 2.24~12.36), nonhomogeneity without a core (P<0.001; OR: 4.31; 95% CI: 2.08~8.92), RPE damage (P<0.001; OR: 28.12; 95% CI: 9.43~83.85) and EZ damage (P<0.001; OR: 14.01; 95% CI: 5.28~37.18) were significantly associated with active change; drusen with low reflectivity (P=0.01; OR: 2.95; 95% CI: 1.29~6.75) and decreased overlying RPE reflectivity (P<0.001; OR: 21.67; 95% CI: 9.20~51.02) were independent predictors for progression. Drusen with high reflectivity were significantly associated with stabilization (P=0.03; OR: 0.17; 95% CI: 0.04~0.84). Conclusions SD-OCT is an optimized, accurate and efficient method to follow up drusen. The intermediate nonexudative AMD patient prognosis was most strongly correlated with druse reflectivity and disruption of the overlying RPE layer. Drusen with low reflectivity and overlying RPE damage were more likely to progress and required frequent follow-up.